Peculiar Confrontations of Islam and Christianity on the Example of Selected Texts of the Oral Culture of the South Slavs - Krzeszewska, Karolina (Phantom of Muhammad, Shade of Samuel Byzantine Empire in Relation to Members of Other Cultures and Religions (7th–15th c.): No. XXXIX, 2020)
The paper concerns the rich and diverse resource of South Slavic folk songs which narrative has been marked by the Turkish invasion.